HETEROLOGOUS EXPRESSION OF MSHSP23, A MEDICAGO SATIVA SMALL HEAT SHOCK PROTEIN, ENHANCES HEAT STRESS TOLERANCE IN CREEPING BENTGRASS - K. W. Lee; J. Y. Cha; J. Y. Mun; B. H. Lee; Y. G. Kim; S.H. Lee (Journal of Animal and Plant Sciences, 2015)
Small heat shock proteins (Hsps) are conserved in living organisms. They exist in diverse subcellular organelles and play important roles in plant defense systems against various abiotic stresses. Chaperone properties of small Hsps have been widely known to prevent the stress-induced denaturation of substrate proteins in cells. Here, we examined the capacity ofMsHsp23to confer tolerance to heat stress (thermotolerance)by heterologous expression in creeping bentgrass. We generated nine independent transgenic creeping bentgrass plants. Two independent transgenic plants (Tg-1 and Tg-2) were examined forthermotolerance (42°C/24h).This resulted in minimal wilting ofthe leaves, which retained healthy green color, while the non-transformed (NT) plants wilted and showed light-green color of their leaves. Plants overexpressing MsHsp23 displayed higher ascorbate peroxidase (APX) activities. Therefore, we conclude that heterologous expression of MsHsp23 in creeping bentgrass can protect plants against heat stress, presumably bychaperone activity that allows for induction of APX.
Keywords: Small Heat-shock protein; Thermotolerance; Creeping bentgrass; Antioxidant enzymes